Domestic Violence: Parental Alienation and Emotional Distress in Families - Oluwaseun Jegede (International Seminar on Social Work Update, 2023)
The dynamics of emotional violence inside a family are investigated in this study. The term "parental alienation" refers to the process by which one parent intentionally influences a child to dislike the other parent. This can happen in either or both households. A number of academics have arrived at the conclusion that this behavior constitutes child abuse, while others have identified it as a type of domestic violence that occurs in families. According to the findings of this study, there has been very little research done on the subject of parental alienation, and parents can sometimes find themselves in the role of either the alienating parent or the targeted parent. As a result, this research examines previous empirical studies on the topic of parental alienation in an effort to increase awareness of the issue within families. Keywords: parental alienation, emotional distress, family domestic violence